Molecular regulatory mechanisms underlying the adaptability of polyploid plants. (24th October 2020) - Scarrow, Margaret; Wang, Yiling; Sun, Genlou
ABSTRACT: Polyploidization influences the genetic composition and gene expression of an organism. This multi‐level genetic change allows the formation of new regulatory pathways leading to increased adaptability. Although both forms of polyploidization provide advantages, autopolyploids were long thought to have little impact on plant divergence compared to allopolyploids due to their formation through genome duplication only, rather than in combination with hybridization. Recent advances have begun to clarify the molecular regulatory mechanisms such as microRNAs, alternative splicing, RNA‐binding proteins, histone modifications, chromatin remodelling, DNA methylation, and N 6 ‐methyladenosine (m6A) RNA methylation underlying the evolutionary success of polyploids. Such research is expanding our understanding of the evolutionary adaptability of polyploids and the regulatory pathways that allow adaptive plasticity in a variety of plant species. Herein we review the roles of individual molecular regulatory mechanisms and their potential synergistic pathways underlying plant evolution and adaptation. Notably, increasing interest in m6A methylation has provided a new component in potential mechanistic coordination that is still predominantly unexplored. Future research should attempt to identify and functionally characterize the evolutionary impact of both individual and synergistic pathways in polyploid plant species.